2022
DOI: 10.3390/nano12050748
|View full text |Cite
|
Sign up to set email alerts
|

Insulation Performance and Simulation Analysis of SiO2-Aramid Paper under High-Voltage Bushing

Abstract: The long-term safe and stable operation of oil-impregnated paper (OIP) bushings is of great significance to the operation of power systems. With the growth of OIP bushing, its internal insulation will gradually decay. Aramid insulation paper has excellent thermal aging characteristics and its insulation performance can be improved by using nano-modification technology. In this paper, the nano-SiO2 particles were used as the modified additives, and the modified aramid insulation paper was prepared through four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…1(i), demonstrating the formation of ZIF-8. 39,40 The combined FT-IR, XRD, SEM, and XPS results indicated that APHZ was successfully synthesized.…”
Section: Structural Characterization Of Aphzmentioning
confidence: 99%
“…1(i), demonstrating the formation of ZIF-8. 39,40 The combined FT-IR, XRD, SEM, and XPS results indicated that APHZ was successfully synthesized.…”
Section: Structural Characterization Of Aphzmentioning
confidence: 99%
“…The heat-resistant insulating paper is primarily used for slot wedge insulation, phase insulation in electric machines, and inter-turn insulation in transformers for high-speed railways [1][2][3][4][5]. Currently, aramid insulating paper [6][7][8][9] and polyimide (PI) insulating paper [10][11][12][13] are widely used as heat-resistant insulating papers. Nomex410 [14,15] is a specific type of high-density meta-aramid paper that is produced by rolling at high temperatures and under high pressure.…”
Section: Introductionmentioning
confidence: 99%